Die etiek van regstellende aksie - J. M. Vorster (Acta Theologica)
This article addresses the ethics of affirmative action in South Africa from a Christian ethical perspective. It firstly evaluates the Biblical teachings of redistributive justice and the implications of these teachings for a modern ethical view of affirmative action. The judicial foundation and the outcome of the process of affirmative action thus far is evaluated in the light of the deontological and consequential theories of ethics. The conclusion is that although affirmative action can be justified in principle, the outcome of the process has many deficiencies and does not serve the purpose of reconciliation. The article concludes with a presentation of guidelines for fair and justifiable affirmative action in South Africa within the context of Christian ethics and legal philosophical principles.